Natural bio-convective flow of Sisko nanofluid subject to gyrotactic microorganisms and activation energy. (5th September 2019) - Khan, M Ijaz; Haq, Fazal; Hayat, T; Alsaedi, A; Rahman, Mujeeb Ur
Abstract: In this communication, we have used the concept of microorganisms to stabilize the suspended nanoparticles in flow of Sisko nanofluid. Bio-convection through mutual effects of buoyancy forces and applied magnetic field is accounted. The flow behavior is discussed over a stretchable surface of cylinder. Furthermore, nonlinear radiative heat flux, dissipation and Joule heating effects are considered for the modeling of energy expression. At the boundary thermal and solutal stratification conditions are considered. Chemical reaction with activation energy is also taken at the surface. Boundary layer concept is used to obtain the nonlinear flow expressions. Total residual error is obtained through OHAM technique. Impacts of physical parameters are graphically discussed. Engineering quantities like skin friction, Sherwood and Nusselt numbers are examined graphically. The obtained result shows that the temperature of the material particles increase against larger values of radiative parameter, Brownian diffusion, Eckert number and thermophoretic parameter. Furthermore, motile density decreases against microorganism's concentration difference and motile stratified parameters.